2016
DOI: 10.1002/2015gl067599
|View full text |Cite
|
Sign up to set email alerts
|

Basin scale controls on CO2 and CH4 emissions from the Upper Mississippi River

Abstract: The Upper Mississippi River, engineered for river navigation in the 1930s, includes a series of low‐head dams and navigation pools receiving elevated sediment and nutrient loads from the mostly agricultural basin. Using high‐resolution, spatially resolved water quality sensor measurements along 1385 river kilometers, we show that primary productivity and organic matter accumulation affect river carbon dioxide and methane emissions to the atmosphere. Phytoplankton drive CO2 to near or below atmospheric equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 38 publications
5
47
2
Order By: Relevance
“…The main stem Mississippi River downstream of the UMR tributaries is capable of large-scale CO 2 undersaturation [Crawford et al, 2016]. These conditions may serve to inhibit in-stream degradation of OM as well as autotrophic production in tributaries, resulting in increased rates of biological activity in the main stem.…”
Section: Processing Of Carbon During Downstream Transportmentioning
confidence: 99%
“…The main stem Mississippi River downstream of the UMR tributaries is capable of large-scale CO 2 undersaturation [Crawford et al, 2016]. These conditions may serve to inhibit in-stream degradation of OM as well as autotrophic production in tributaries, resulting in increased rates of biological activity in the main stem.…”
Section: Processing Of Carbon During Downstream Transportmentioning
confidence: 99%
“…2; Tables S2, S3) require a cautious assessment of dam effects, the higher values of CH 4 and N 2 O measured in some dams and outflows compared to upstream levels indicate dam-specific conditions driving the production and consumption of CH 4 and N 2 O in reservoir water or sediments. Crawford et al (2016) observed a weak summer-330 time CO 2 sink due to enhanced photosynthesis but elevated concentrations and fluxes of CH 4 along the upper Mississippi River reaches impounded by a series of low-head dams. They attributed the observed supersaturation in CH 4 to anaerobic conditions in organic-rich sediments.…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 99%
“…The trapping 70 of sediments and nutrients in reservoir sediments, combined with increased water retention time and improved light conditions promoting primary production, can alter significantly the rate of production and consumption of CO 2 and CH 4 in impounded waters (Maavara et al, 2017). Many studies have examined impoundment effects on GHG emissions from various types and sizes of dams including hydroelectric dams, often reporting contrasting results such as large pulse emissions of CO 2 and CH 4 from the flooded vegetation and sediments following dam construction and an enhanced primary production and CO 2 sink in 75 eutrophic reservoirs (Abril et al, 2005;Chen et al, 2009;Barros et al, 2011;Hu and Cheng, 2013;Maeck et al, 2013;Crawford et al, 2016;Maavara et al, 2017;Shi et al, 2017). These contrasting impoundment effects can be explained by the shifting balance between autotrophy and heterotrophy at diel to decadal timescales (Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In extreme cases of wastewater pollution, anoxic conditions will lead to low N 2 O levels due to denitrification (Rajkumar et al, 2008), but in oxic conditions nitrification fuelled by NH 4 + inputs from wastewater leads to N 2 O production (Garnier et al, 2009;Yu et al, 2013;Marwick et al, 2014). Impoundments increase water residence time that favour organic matter sedimentation and CH 4 production (Maeck et al, 2013;Crawford et al, 2016). Increased water residence time and water transparency due to impoundments can lead to low CO 2 levels related to enhanced primary production .…”
Section: Introductionmentioning
confidence: 99%